Degradation of Chloramphenicol with Novel Metal Foam Electrodes in Bioelectrochemical Systems - Wu, Dan (2017)
Bioelectrochemical system (BES) has been considered as one of the efficient methods for recalcitrant organic pollutant removal. This study compared three different cathodes, i.e. carbon rod (CR), copper foam (Cu), nickel foam (NF), for chloramphenicol (CAP) removal in BESs, while Cu and NF have not been used as cathodes for CAP degradation before. The results demonstrated that with 0.3 V applied voltage, 100% removal of 32 mg L−1 CAP was observed after 36 h and 24 h with CR and Cu electrodes respectively, while amines were the main intermediate products. The performance of Cu cathode was 15.13 times better than NF electrode under 0.3 V applied voltage. When the applied voltage increased to 0.5 V, CAP could be completely removed within 12 h with Cu electrode, while complete CAP removal was found after 24 hours for CR and more than 120 hours for NF respectively. With 0.5 V applied voltage in 24 h degradation period, the final degradation products were found to be CO2 and H2O for Cu electrode, while nitrobenzene and 4-Nitrobenzyl alcohol were the main products for CR and NF electrodes respectively. The results demonstrated that Cu was the most efficient cathode for CAP degradation.